Preparation of Copper extractant Salicylaldoxime from Willow tree barks and leaves - San, Myint; Khairel Rafezi, Ahmad; Shaiful Rizam, Shamsudin; Ruhiyuddin, Mohd Zaki; Mar Mar, Wai (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.